PERAN GURU DALAM MENINGKATKAN COMMUNICATION SKILL PESERTA DIDIK ABAD 21 - Ammar Zaki; Akhyar Akhyar; Samsuar Samsuar; Syarifah Farissi Hamama; Dwi Wahyu Kartikasari; Ade Irfan (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This article aims to describe the teacher's role in improving students communication skills in the 21st century which was carried out at SMA 1 Jaya. The approach used in this research is a qualitative approach with a case study research design. The subjects in this study were teachers who taught at SMA 1 Jaya. Data collection techniques using interviews were carried out on teachers or educators as the first informants who were considered capable of understanding the abilities of their students, as well as the strategies used by teachers to improve students' communication skills both in the realm of formal learning. Data analysis using mile and hubberman which data reduction, data presentation, and conclusions. The results of the study show that teachers have a major role in schools in improving students communication skills in facing the challenges of the 21st century where teachers engage in active learning based on student center learning. The learning that has been carried out has been effective in improving students communication skills, but it requires an increase in the teacher's creativity in developing the learning process.